Effects of vascular endothelial growth factor (VEGF-A) and endostatin on bone - Sipola, A. (Annina) (University of Oulu, 2009)
Abstract Angiogenesis is essential for the replacement of cartilage by bone during skeletal growth and regeneration. Vascular endothelial growth factor-A (VEGF-A) is a key regulator of angiogenesis whereas endostatin, a potent inhibitor of endothelial cell proliferation and migration, is a natural antagonist of VEGF-A. The regulatory roles of these peptides in angiogenesis, bone formation and bone cells were investigated in this study.